LANDSCAPE IN THE ESSAY "BOBOTOG": ARTISTIC EXPRESSION IN THE IMAGE OF FLORA (Scientific journal of the Fergana State University, 2025)
The article analyzes the landscape imagery in Mengziyo Safarov’s essay Bobotog, with a focus on the artistic depiction of flora. The value of the work lies in its reflection on the ancient history of the Surkhan oasis and its connection to contemporary ecological challenges. In the era of globalization, the relationship between nature and humanity becomes increasingly complex and profound. The essay portrays a harmonious relationship between humans and nature, emphasizing that human development is deeply rooted in the natural world — a theme conveyed through aesthetic and literary means.